Infected Kin : Orphan Care and AIDS in Lesotho. - Block, Ellen (Mary Ellen) (Medical anthropology (New Brunswick, N.J.), 2019)
AIDS has devastated communities across southern Africa. In Lesotho, where a quarter of adults are infected, the wide-ranging implications of the disease have been felt in every family, disrupting key aspects of social life. In Infected Kin, Ellen Block and Will McGrath argue that AIDS is fundamentally a kinship disease, examining the ways it transcends infected individuals and seeps into kin relations and networks of care. While much AIDS scholarship has turned away from the difficult daily realities of those affected by the disease, Infected Kin uses both ethnographic scholarship and creative nonfiction to bring to life the joys and struggles of the Basotho people at the heart of the AIDS pandemic. The result is a book accessible to wide readership, yet built upon scholarship and theoretical contributions that ensure Infected Kin will remain relevant to anyone interested in anthropology, kinship, global health, and care.